3D finite element analysis and optimization of welding residual stress in the girth joints of X80 steel pipeline. (June 2021) - Zhao, Weimin; Jiang, Wei; Zhang, Hongjie; Han, Bin; Jin, Haicheng; Gao, Qi
Highlights: 3D FE models were developed to predict residual stress in girth welded large pipe. Tensile stress exceeding 62 % R t0.5 of steel was considered as dangerous stress. The peak stress and high-stress area in four typical girth joints were analyzed. Reasonable welding procedure and surface impacting treatment are recommended. Abstract: The distribution of welding residual stress is the basis of controlling environmental cracking failure in the joint area of steel pipeline. In this study, 3D actual-size finite element models were developed for X80 steel pipe to predict the welding stress field in four typical girth joints. Electrochemical measurements under multi-stage loading revealed the relationship among tensile stress level, dislocation multiplication, and corrosion. The increased number of weld passes reduced the peak residual stress, and the adopted fully automatic welding decreased the high-stress zone where dislocation multiplication might occur. Therefore, adopting automatic welding and moderately increasing the number of weld passes are recommended to control welding residual stress.